Accuracy of sequential sub-field synchronization of multiple digital camcorders through numerical optimization - Christopher, G. A.; Yoon, S.; Kwon, Y. (Sports Biomechanics, 2008)
The use of digital camcorders in biomechanical analyses can introduce errors due to inter-camera time offsets. The faster the motion being recorded the greater the error. A sequential synchronization method was developed in this study to achieve sub-field camera synchronization for multiple camcorders through numerical optimization. A recreational golfer performed ten drives while being recorded with four digital camcorders (60-Hz sampling rate). Video signals were sampled at 10,000 Hz to determine the actual inter-camera time offsets. The optimized inter-camera time offsets were computed based on three markers placed on the shaft, each separated by 200 mm. The inter-camera time offset error was computed as the difference between the optimized and actual inter-camera time offsets. The inter-camera time offset error reduced on average from 0.518 to 0.019 fields (1 field = 16.7 ms) or less due to sequential optimization. The optimized global reconstruction errors were less than 19% of the unadjusted values. It was concluded that the ability to synchronize multiple (two or more) cameras using a sequential sub-field optimization strategy promises to extend the use of relatively inexpensive digital camcorders to motions considered too fast for the low field rates of such cameras. The sequential approach presented provides a balance between computation time and reconstruction accuracy.